Platinum surface complexes as precursors for H–O recombination catalysts - Olesya B Volovenko; Olga A Zaporozhets; Vladyslav V Lisnyak; Olga Yu Boldyrieva (Adsorption Science & Technology)
In this work, the adsorption of platinum (II, IV) chloride complexes from acidic solutions on silica gel modified with quaternary ammonium salts (QAS) was studied. The uptake of the platinum chloride complexes is caused by the formation of ionic (QAS + ) 2 [PtCl x ] 2− ( x  = 4, 6) associates on the surface of silica gel. The isotherms of adsorption are fitted by the Langmuir model. The maximum capacity for [PtCl 4 ] 2− and [PtCl 6 ] 2− is 0.99 and 1.13 mmol/g, correspondingly. The respective adsorption constants K L  = 6.8 and 10 × 10 5  l/mol prove the high affinity of the adsorbates to the QAS-modified surface. Platinum metal nanoparticles supported on the surface of the silica gel were prepared by reducing the adsorbed platinum (II, IV) complexes. Such nanoparticles functioning at the moderate temperature regime have demonstrated a reasonable catalytic activity for the hydrogen and oxygen recombination, and an excellent stability over 35 cycles of the reaction.